The Clinical Case of Lactate-acidosis with Fatal Outcome in a Patient with 2 Type Diabetes - Olga Yu. Ibragimova; Diana Sh. Avzaletdinova; Tatiana V. Morugova; Elena R. Vlasova; Nataliya G. Kharina; Zukhra G. Girfanova (LLC "MEDIAFORMAT", 2021)
At the moment, lactate-acidosis coma in patients with diabetes mellitus is considered a rare and extremely urgent condition that occurs in patients with concomitant diseases as well as when taking the most widely used sugar reducing drug - metformin. This article describes a case of lactate-acidosis coma with a fatal outcome, which occurred against the background of taking metformin and alcohol abuse, in a woman with type 2 dia-betes mellitus aged 48 years.